2010
DOI: 10.1007/s11926-009-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Pulmonary Fibrosis in Systemic Sclerosis: Lessons from Interstitial Lung Disease

Abstract: Interstitial lung disease is a frequent complication of systemic sclerosis and currently is the leading cause of death. Our ability to predict which individuals are at greatest risk of developing clinically significant, progressive interstitial lung disease remains inadequate. Identification of circulating autoantibodies and other biomarkers, as well as genetic polymorphisms and aberrant gene expression, all hold promise as diagnostic and prognostic tools, as well as therapeutic targets. Many practice patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
7
1
2
Order By: Relevance
“…The opposite from what is reported in other studies is also observed for several of these genes in this study. For example, hypermethylation of both FLI1 in SSc and SOCS1 in SLE was not observed in our study even though hypermethylation of promoter regions of both genes has been previously implicated in the pathophysiology of SSc and SLE, respectively [ 40 - 42 ]. However, FLI-1 overexpression, probably as a result of promoter hypomethylation, has been detected in various types of cancer and other diseases [ 43 ].…”
Section: Discussioncontrasting
confidence: 71%
“…The opposite from what is reported in other studies is also observed for several of these genes in this study. For example, hypermethylation of both FLI1 in SSc and SOCS1 in SLE was not observed in our study even though hypermethylation of promoter regions of both genes has been previously implicated in the pathophysiology of SSc and SLE, respectively [ 40 - 42 ]. However, FLI-1 overexpression, probably as a result of promoter hypomethylation, has been detected in various types of cancer and other diseases [ 43 ].…”
Section: Discussioncontrasting
confidence: 71%
“…However, it has been recognized that the most serious clinical manifestations of the disease and its high mortality are the result of SSc-associated-interstitial lung disease (ILD) or pulmonary arterial hypertension (PAH). SSc-associated ILD results from exaggerated and often progressive accumulation of fibrous collagens and other extracellular matrix molecules in the lung parenchyma, whereas, SSc-associated PAH is caused by functional alterations and structural fibroproliferative vasculopathy affecting the small and medium sized pulmonary arterioles [812]. …”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary fibrosis is characterized by the accumulation of fibroblasts and extracellular matrix (ECM) in the lung (5)(6)(7)(8)(9). The disorder arises from a variety of etiologies that initiate inflammation (9)(10)(11) and excess production of inflammatory cytokines (e.g., IL-1b, IL-6), which promote the progression to lung fibrosis (10,11).…”
mentioning
confidence: 99%